Analysis of potential drug interactions and their management in hypertensive patients receiving coronary heart disease medications at x hospital, Jambi city, Indonesia - Secio Lovellya; Jelly Permatasari; Rahmadha Trifah (International Journal on Health and Medical Sciences, 2026)
Hypertension is a chronic condition that may lead to various complications, including coronary heart disease (CHD). Patients with hypertension complicated by CHD commonly receive multiple medications, thereby increasing the risk of potential drug interactions that may compromise therapeutic efficacy or increase the incidence of adverse drug reactions. This study aimed to analyze the potential drug interactions based on their mechanisms and severity levels, as well as to describe the strategies used to manage these interactions among hypertensive patients receiving CHD medications at X Hospital, Jambi City. A descriptive retrospective study was conducted using outpatient medical records collected between January and December 2025. A total of 93 patients who fulfilled the inclusion and exclusion criteria were enrolled. Potential drug interactions were identified using the Drugs.com Drug Interaction Checker. The findings revealed that most patients were male and aged over 65 years. Prescriptions containing six to seven medications accounted for the highest proportion (56.99%). Based on severity, moderate interactions predominated, accounting for 507 cases (69.26%), followed by minor interactions with 167 cases (22.81%) and major interactions with 58 cases (7.92%). Regarding the underlying mechanism, pharmacodynamic interactions were considerably more frequent than pharmacokinetic interactions, representing 687 cases (93.85%) and 45 cases (6.15%), respectively. The combination of aspirin and bisoprolol was identified as the most frequently encountered drug interaction, occurring in 61 cases. Management of potential drug interactions primarily involved therapeutic monitoring and regular clinical evaluation to optimize treatment safety and effectiveness.